Literatura română veche. Priorităţi ale cercetării academice actuale - Gh. Chivu (Revista de Istorie și Teorie Literară)
The study reviews the issues raised by the investigation and reevaluation of old Romanian literature during a time of pronounced and noticeable crisis of humanistic research and outlines the objectives for the Romanian philologic research.